Delineating and sparing functional nephrons for radiotherapy in the case of lymphoma with polycystic kidney disease - Venkada Manickam Gurusamy; Suparna Halsnad Chandramouli; Muhammad Usman; Saju Raveendran Divakar; Rabih Wafiq Hammoud; Noora Al-Hammadi (Cancer Treatment and Research Communications, 2022)
Purpose:: It is imperative to spare functioning kidneys from high radiation doses when they are near enough to radiotherapy (RT) target volumes in patients with polycystic kidney disease (PKD). To achieve this intent, we designed the unique approach that we report here. Methods and materials:: The patient who has PKD, presented with B-cell lymphoma involving paraaortic lymph nodes. After completing chemotherapy, RT was planned to the residual nodal disease. The diagnostic positron emission tomography computed tomography (PETCT) scan was fused with the RT planning CT scan. 18F-2-deoxy-2(F)-fluro-d-glucose (FDG) avid active kidneys were contoured separately, and the treatment plan was optimized to avoid these volumes. Results:: The functional volume was 17.52% of the right kidney whereas it was 7.44% of the left. The mean doses were 4.61 Gy and 4.2 Gy, respectively. The baseline estimated glomerular filtration rate (eGFR) was >60 mL/min; at 18 months follow-up, it was 62 mL/min. Conclusions:: Delineation of functional nephrons was feasible while utilizing the staging FDG-PETCT scan for radiotherapy contouring in our patient, which aided to achieve the optimal dose-volume constraints. Further studies are warranted to analyze and quantify the benefit of this easily accessible method in the future.